Exploring moral perception and mind uploading in Kazuo Ishiguro's ‘Klara and the Sun': ethical-aesthetic perspectives on identity attribution in artificial intelligence - Echarte Alonso, Luis E. (Frontiers in Communication, 2023)
Literature wields a profound influence on our cognitive processes, shaping not only how we think but also what we think about (Vaccaro et al., 2021;Pino and Mazza, 2016;Kidd and Castano, 2013). Aesthetic experiences, in particular, seem to foster a positive impact on our ability to comprehend complexity (Starr, 2023;Adamaszek, Cattaneo, Ciricugno, Chatterjee, 2022). This influence underscores the significant role of literature in the exploration of value learning and ethics research, because evaluating any decision-making requires seeking the widest possible frame of reference. Furthermore, literature plays a pivotal role in enriching our perception of both the external world and our inner selves, thereby fostering a heightened sense of ethical discernment. In this paper, I explore this last idea by examining Kazuo Ishiguro's Klara and the Sun. In this enquiry, I reveal connections between two crucial controversies surrounding mind uploading: the epistemological debate centered on the theory of moral perception and the ontological inquiry into personal identity. Researching the intersection of these two big issues guide my decision to employ conceptual synthesis as the methodological framework. Besides, I will argue that the ideas of moral perception and personal identity that emerges in Ishiguro's dystopia are in tune with the narrativist hypothesis of Charles Taylor. In my conclusions, I defend that prospect of replacing a human being with a robot hinges on the challenge of instilling the machine with a unique moral perception. This remains an elusive goal, perhaps perpetually so, due to the inherent impossibility of objectifying a machine capable of apprehending and processing the non-objective qualities of matter. Furthermore, even if we were able to create such a machine, it would likely resist assuming a substitutive role, as it would quickly discover and appreciate its own existence. Finally, I ponder the implications of mistaking a simulation of human for an authentic replica, namely, an unsuccessful and unnoticed attempt at mind uploading -loneliness.